RETRACTED: Ossicini, A. On the Nature of Some Euler’s Double Equations Equivalent to Fermat’s Last Theorem. Mathematics 2022, 10, 4471 - Andrea Ossicini (Mathematics)
The Mathematics Editorial Office retracts the article entitled “On the Nature of Some Euler’s Double Equations Equivalent to Fermat’s Last Theorem [...]